Explaining local variation in referrals from health services to children's social care in England 2013–16: a study using 'children in need' administrative data. (18th June 2019) - Emmott, E H; Mc Grath-Lone, L; Harron, K; Woodman, J
Abstract: Background: Referral rates from Health service to Children's Social Care (CSC) services vary across England. In 2019, the National Audit Office (re)iterated the urgent need to understand the drivers of such variation. Methods: Using administrative data (Children in Need Census, 2013–16), we calculated annual referral rates from Health to CSC services (Health referral rate) by Local Authority (LA) areas. We used multilevel linear regression to investigate the relationship between age-adjusted Health referral rates and local need (demand factors) and local practice/systems (supply factors). We present a tool to compare unadjusted and adjusted LA rates. Results: There was high LA variation in Health referral rates, particularly for infants (mean = 29.0/1000 children < 1 y; range = 6.5–101.8; sd = 12.4). LA variation persisted after age-adjustment. Child poverty (local need) and overall referral rate (local practice/systems) explained 60% of variation in age-adjusted Health referral rates. Overall referral rate was the strongest predictor. Adjusted referral rates were substantially different from unadjusted rates. After adjustment, 57.7% of LAs had higher/lower Health referral rates than expected. Conclusions: While higher levels of local need are associated with higher Health referrals, some areas have high Health referrals irrespective of local need . Our tool demonstrates the benefits of using adjusted rates to compare LAs.